2022
DOI: 10.26434/chemrxiv-2022-x2qxq
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Comparative Evaluation of Indirect Sequence-Specific Magnetoextraction-aided Fluorescence and Electrochemical LAMP with SARS-CoV-2 Nucleic Acid as the Analyte

Abstract: Since the beginning of the SARS-CoV-2 pandemic, nucleic acid amplification test (NAAT) such as quantitative real-time reverse transcriptase PCR (qRT-PCR) has remained the primary intervention for diagnostics and containment of SARS-CoV-2. Despite its remarkable clinical as well as analytical specificity and sensitivity, qRT-PCR necessitates pure nucleic acid free of any polymerase inhibitors (from complex biological matrices) as its substrate. Similarly, isothermal NAATs (iNAATs), despite their advantage over … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…In a separate manuscript from our groups currently undergoing peer review (uploaded with this manuscript 40 ), we have demonstrated the utility of the indirect magnetocapture over the direct magnetocapture in terms of assay performance. The working scheme of the indirect magnetocapture, the one utilized in this manuscript has been illustrated in Figure 8.…”
Section: Magnetocapture Of Sars-cov-2 Rdrp Plasmid Dna and Rnamentioning
confidence: 99%
See 4 more Smart Citations
“…In a separate manuscript from our groups currently undergoing peer review (uploaded with this manuscript 40 ), we have demonstrated the utility of the indirect magnetocapture over the direct magnetocapture in terms of assay performance. The working scheme of the indirect magnetocapture, the one utilized in this manuscript has been illustrated in Figure 8.…”
Section: Magnetocapture Of Sars-cov-2 Rdrp Plasmid Dna and Rnamentioning
confidence: 99%
“…The experiments concerning the LAMP primer optimization and assays have been described in detail in a separate manuscript from our groups currently undergoing peer review (uploaded with this manuscript 40 ). Briefly, the LAMP assay involved 0.4 μM outer primers, 0.332 μM forward and backward inner primer, 1 μM forward loop primers and 0.4 μM back loop primers in their final concentration 41 were conducted in real-time PCR (64C for 1 h, with fluorescence monitoring every 1 min, followed by melting curve analysis) or thermal cycler (64C for 1 h followed by 85C for 20 min), respectively.…”
Section: Primer Optimization Fluorescence and Electrochemical Lamp As...mentioning
confidence: 99%
See 3 more Smart Citations